NEURAL NETWORK FUNDAMENTAL DAN IMPLEMENTASI DALAM PEMROGRAMAN - Ibnu Akil (INTI Nusa Mandiri, 2020)
Nowadays machine learning and deep learning are becoming a trend in the world of information system. They are actually is part of an artificial intelligence domain. However, so many people don’t understand that machine learning and deep learning are built using neural networks. Therefore, in order to understand how machine learning and deep learning works, we must understand the basic concept of the neural network first. In this article, the writer describes the basic theory, math function of a neural network, and the example of implementation into the java programming language. The writer hopes that this article may help to understand neural network which is the core of machine learning and deep learning.